2012
DOI: 10.1021/es301269k
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Mount Simon Sandstone and the Eau Claire Shale Under CO2 Storage Conditions

Abstract: The Mount Simon sandstone and Eau Claire shale formations are target storage and cap rock formations for the Illinois Basin-Decatur Geologic Carbon Sequestration Project. We reacted rock samples with brine and supercritical CO(2) at 51 °C and 19.5 MPa to access the reactivity of these formations at storage conditions and to address the applicability of using published kinetic and thermodynamic constants to predict geochemical alteration that may occur during storage by quantifying parameter uncertainty against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
77
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(87 citation statements)
references
References 27 publications
(52 reference statements)
10
77
0
Order By: Relevance
“…By comparison, clay minerals and feldspars did not react, possibly because the carbonate reactions prevented low pH conditions from being attained. In contrast, experiments by Carroll et al (2013) on sandstone and shale at 51 o C and 19.5 MPa found that Fe-rich clays appear to have dominated the reactions, dissolving incongruently to secondary clays and amorphous silica.…”
Section: Reservoir and Cap Rocksmentioning
confidence: 81%
See 1 more Smart Citation
“…By comparison, clay minerals and feldspars did not react, possibly because the carbonate reactions prevented low pH conditions from being attained. In contrast, experiments by Carroll et al (2013) on sandstone and shale at 51 o C and 19.5 MPa found that Fe-rich clays appear to have dominated the reactions, dissolving incongruently to secondary clays and amorphous silica.…”
Section: Reservoir and Cap Rocksmentioning
confidence: 81%
“…Most data are for far from equilibrium conditions, but Davis et al (2011) While quartz dissolution rates should be rather slow, Houston et al (2007) reported evidence for silica dissolution into injected seawater during a seawater enhanced oil recovery operation in the Miller Field, UK North Sea, but suggested that it was released from feldspars or other silicate minerals, rather than directly from quartz dissolution. Carroll et al (2013), in a study of reactivity of reservoir and caprocks with CO 2 , even reported amorphous silica precipitation from silica released during clay transformations. Overall, injection of CO 2 into existing formation waters is unlikely to have a significant effect on the amount of silica in solution, although it may lead to silica being redistributed from feldspars to clays.…”
Section: Quartzmentioning
confidence: 99%
“…Quartz dissolution is calculated using the Si concentration changes while the amount of illite is evaluated using the amount of K concentration. No precipitations of other clay minerals such as kaolinite are considered here, even if in other recent studies kaolinite precipitation has been considered the most favourable secondary alteration mineral [49][50][51]. Here, we stipulate that without alumino-silicate in the initial rock sample such as albite or microcline, kaolinite precipitation is not expected.…”
Section: Mass Balance Calculation and Numerical Modellingmentioning
confidence: 91%
“…This gap may arise from the uncertainties of rate constant, mass fraction of minerals, reactive surface area, and thermodynamic data [35,36]. Nonetheless, we consider that the modeling results are acceptable considering only dissolution/precipitation of the minerals (Table 3).…”
Section: Ion Concentrationsmentioning
confidence: 99%